2004
DOI: 10.1023/b:viru.0000012266.04871.ce
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Vaccination of Mice with Plasmids Encoding the NS1 Non-structural Protein from Tick-borne Encephalitis Virus and Dengue 2 Virus

Abstract: Although there is a safe, inexpensive and efficacious vaccine against yellow fever, vaccination against other flavivirus diseases is less successful. There is no licensed vaccine against dengue fever and current vaccines against tick-borne encephalitis (TBE) and Japanese encephalitis are expensive and require several injections. Furthermore novel vaccines containing only virus envelope proteins may raise fears over antibody mediated enhancement (ADE) of disease. Here we report the successful use of genetic vac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
2

Year Published

2006
2006
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 67 publications
0
14
0
2
Order By: Relevance
“…The majority of DENV-specific T-cell epitopes are recognized by CD8 þ T cells (97). This result is not surprising given the presumed role of CD8 þ T cells in viral clearance and their potential role in immunopathology (although CD4 þ T cells have also been implicated in the latter).…”
Section: Phenotype Categories Of Flavivirus Epitopesmentioning
confidence: 68%
See 2 more Smart Citations
“…The majority of DENV-specific T-cell epitopes are recognized by CD8 þ T cells (97). This result is not surprising given the presumed role of CD8 þ T cells in viral clearance and their potential role in immunopathology (although CD4 þ T cells have also been implicated in the latter).…”
Section: Phenotype Categories Of Flavivirus Epitopesmentioning
confidence: 68%
“…And indeed, the E protein is believed to play a critical role in the induction of immunity to natural infection (38). Moreover, NS1 has also been shown to mediate protection against disease by inducing both humoral and cellular responses (41,96,97). Although there is no evidence that antibodies are associated with severe disease, non-neutralizing antibodies against E can enhance infectivity in mouse macrophages (72).…”
Section: Tick-borne Encephalitis Virus and Murray Valley St Louis mentioning
confidence: 96%
See 1 more Smart Citation
“…Future studies using error-prone PCR mutagenesis and yeast surface display are planned to identify the amino acid contact residues for many of the individual MAbs against WNV NS1. Because some antibodies against flavivirus NS1 protect against lethal infection in vivo, immunization with purified NS1 has been proposed as an alternative vaccination strategy against flaviviruses (26,33,34,44,62,63,71,75). Indeed, immunization with a single NS1 peptide (amino acids 37 to 55) of TBE elicited antibodies that protected mice against lethal challenge (65).…”
Section: Discussionmentioning
confidence: 99%
“…Although there is a wealth of evidence suggesting protection afforded by NS1 is a result of anti-NS1 antibodies ability to fix complement (Co et al, 2002;Falgout et al, 1990;Schlesinger et al, 1986;Schlesinger et al, 1985Schlesinger et al, , 1987, it has been found protection does not always correlate with the ability of a Mabs to fix complement, suggesting other mechanisms of protection (Henchal et al, 1988;Jacobs et al, 1994;Schlesinger et al, 1993;Young, 1990). Other strategies using NS1 have also been developed including live attenuated virus, recombinant vaccinia virus, adenovirus, subunit vaccines including NS1 with other structural proteins and DNA vaccines with various immunisation schedules have been successfully used to protect mice and monkeys from TBEV, YFV, JEV and DENV (Aleshin et al, 2007;Blaney et al, 2006;Blaney et al, 2003;Calvert et al, 2006;Costa et al, 2007;Costa et al, 2006a;Costa et al, 2006b;Jacobs et al, 1992;Khoretonenko et al, 2003;Lieberman et al, 2007;Mellado-Sanchez et al, 2005;Puttikhunt et al, 2003;Simmons et al, 2006;Timofeev et al, 2004;Timofeev et al, 1998;Wu et al, 2003). The major stumbling block for NS1 vaccines is the fact that NS1 can also elicit autoantibodies that cross react with host proteins and induce damage to uninfected cells.…”
Section: Ns1 Based Vaccinesmentioning
confidence: 99%